Characterisation of uveitis in association with multiple sclerosis - Messenger, Wyatt; Hildebrandt, Anna Lena; Mackensen, Friederike (British journal of ophthalmology, 2015)
Purpose To characterise uveitis in association with multiple sclerosis (MS). - Methods We conducted a retrospective chart review of patients with uveitis and MS at two uveitis centres (Portland, Oregon, USA and Heidelberg, Germany). Baseline characteristics and ophthalmic data were collected at the patient's first and last visits. Additionally, neurological records were obtained when possible. - Results We identified 113 patients (196 eyes) with uveitis and MS. Of these, 53 had a diagnosis of MS confirmed by review of neurological records, 50 additional patients fulfilled the Poser criteria for MS and 10 with MS were referred by an outside neurologist. Among them, 83 (73%) were women and the mean age of presentation was 40.6 years (range 13-64 years). The average visual acuity in affected eyes at presentation was 20/39. There were 90 patients (80%) who presented with intermediate uveitis and 24 patients (15%) with anterior uveitis. Posterior and pan-uveitis were found in four patients (3%) and two patients (2%), respectively. During a median follow-up of 3.2 years (range 0.04-21 years), visual acuity improved -0.09 logMar/year. Compared with our location-matched controls with idiopathic intermediate uveitis (n=16), patients with MS and intermediate uveitis were significantly older when diagnosed with uveitis (p=0.027) and more likely to be female (p=0.01). There was no statistical difference in visual acuity or rate of vision change between our cases and controls (p=0.58 and p=0.36, respectively). - Conclusions Uveitis with MS generally presents as intermediate uveitis with a minority presenting with anterior uveitis. Patients are significantly older and more likely to be women than patients with idiopathic intermediate uveitis. The visual prognosis is generally favourable.
Published online first: 28 August 2014
Gesehen am 29.05.2020